2019
DOI: 10.1021/acs.iecr.9b01906
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Efficient Continuous-Flow Route To Prepare Trifluoromethylated N-Fused Heterocycles for Drug Discovery and Pharmaceutical Manufacturing

Abstract: Continuous-flow processing has become one of the fastest-growing research areas in chemistry in the last 10 years. Herein we disclose an automated and scalable continuous-flow route for the quick introduction of trifluoromethyl groups on a variety of heterocycles, with application in drug discovery and manufacturing. This involves the direct alkylation-cyclization of amines in the presence of trifluoroacetic acid or anhydride, cheap and readily available CF 3 -containing building blocks. Compared to traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Furthermore, it was found that nitrogen-based nucleophiles (6), such as aliphatic amines [25][26][27], anilines [28][29][30][31], or hydrazines [32,33], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [34][35][36]. Employing strategically placed second nucleophilic functionality (carbon or heteroatom-based), the resulting amidinium species (7) can be transformed into a variety of heterocyclic compounds, such as benzoxazoles (8) [23,28] or benzimidazoles (9) [28], perimidines (10) [29], 6,7-dihydro-1H-cyclopenta[gh]perimidines (11) [31], 1,3,4-oxa-di-azoles (12) [32,33], imidazolines (13) [25], 3,4-dihydro-iso-quinolines (14) [27], imidazo [1,5-a]pyridines (15) [26], and [1,2,4]triazolo [4,3-a] It occurred to us that a similar strategy can be applied for the straightforward preparation of 3,4-dihydroquinazolines as well. In reaction with bis-nucleophilic 2-(aminomethyl) anilines (1), the phosphorylated nitronate species 5 would, after elimination of orthophosphoric acid entity, afford an amidinium intermediate 7 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was found that nitrogen-based nucleophiles (6), such as aliphatic amines [25][26][27], anilines [28][29][30][31], or hydrazines [32,33], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [34][35][36]. Employing strategically placed second nucleophilic functionality (carbon or heteroatom-based), the resulting amidinium species (7) can be transformed into a variety of heterocyclic compounds, such as benzoxazoles (8) [23,28] or benzimidazoles (9) [28], perimidines (10) [29], 6,7-dihydro-1H-cyclopenta[gh]perimidines (11) [31], 1,3,4-oxa-di-azoles (12) [32,33], imidazolines (13) [25], 3,4-dihydro-iso-quinolines (14) [27], imidazo [1,5-a]pyridines (15) [26], and [1,2,4]triazolo [4,3-a] It occurred to us that a similar strategy can be applied for the straightforward preparation of 3,4-dihydroquinazolines as well. In reaction with bis-nucleophilic 2-(aminomethyl) anilines (1), the phosphorylated nitronate species 5 would, after elimination of orthophosphoric acid entity, afford an amidinium intermediate 7 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays microfluidics has been used in a wide range of areas, such as health detection [ 1 ], chemical pharmacy [ 2 , 3 ], precision sensors [ 4 ], etc. It is important to investigate the property of microfluidics.…”
Section: Introductionmentioning
confidence: 99%
“…Most synthetic approaches rely on various cyclocondensations of nucleophilic (2-aminomethyl)pyridine precursors, introducing a new five-membered ring. Typically, carboxylic acids [16][17][18][19][20], acyl anhydrides [21][22][23], acyl chlorides [24][25][26][27], esters [28], thioamides [29][30][31], dithionates [32,33], or thiocarbamates [34] are employed as electrophilic components, but oxidative cyclocondensations with aldehydes have also been showcased [35][36][37]. However, given the importance of these targets, new preparative methods are still in high demand.…”
Section: Introductionmentioning
confidence: 99%